Efeitos da estimulação transcraniana por corrente contínua sobre a variabilidade da frequência cardíaca de mulheres hipertensas - Gomes, Luís Paulo de Souza (2011)
The transcranial direct current stimulation (tDCS) is a neuromodulatory technique able to modify cortical excitability and presumably modulate the neural activity of cortical areas involved in autonomic regulation, such as the medial prefrontal cortex (MFPC) and insular cortex (IC). Regarding the ANS, there is evidence of hyper-sympathetic activation in people with HTN. To contribute to the discussion, this thesis was divided as follows: The first chapter titled "Heart rate variability (HRV): analytical methods and their applicability "consists of a review article, aiming at the theoretical foundation about methods of assessment of HRV and its prospects for use. The second chapter consists of an original paper entitled "Effect of transcranial direct current stimulation on heart rate variability in hypertensive women". This research applied anodal tDCS, cathodic and simulated (sham) separately on the left temporal lobe (T3) of hypertensive women showed significant increases in parasympathetic activity, only with the application of cathodic tDCS. However, one cannot say which specific area of the brain was responsible for variations in HRV, since the two electrodes were about regions involved in autonomic control and still not know what the real impact of bipolar stimulation on brain physiology. Although there are limitations, our results may assist in developing a new tool to explore noninvasively the autonomic nervous system, and even open new therapeutic perspectives for treatment of their disorders such as hypertension.